Dynamic changes in Shiga toxin (Stx) 1 transducing phage throughout the evolution of O26:H11 Stx-producing Escherichia coli - Bungo Yano; Itsuki Taniguchi; Yasuhiro Gotoh; Tetsuya Hayashi; Keiji Nakamura (Scientific Reports, 2023)
Abstract Shiga toxin (Stx) is the key virulence factor of Stx-producing Escherichia coli (STEC). All known Stxs (Stx1 and Stx2) are encoded by bacteriophages (Stx phages). Although the genetic diversity of Stx phages has frequently been described, systematic analyses of Stx phages in a single STEC lineage are limited. In this study, focusing on the O26:H11 STEC sequence type 21 (ST21) lineage, where the stx1a gene is highly conserved, we analysed the Stx1a phages in 39 strains representative of the entire ST21 lineage and found a high level of variation in Stx1a phage genomes caused by various mechanisms, including replacement by a different Stx1a phage at the same or different locus. The evolutionary timescale of events changing Stx1a phages in ST21 was also determined. Furthermore, by using an Stx1 quantification system developed in this study, we found notable variations in the efficiency of Stx1 production upon prophage induction, which sharply contrasted with the conserved iron regulated Stx1 production. These variations were associated with the Stx1a phage alteration in some cases but not in other cases; thus, Stx1 production in this STEC lineage was determined by differences not only in Stx1 phages but also in host-encoded factors.